Risk Attitude and Time Preference in Health - Gafni, Amiram; Torrance, George W. (Management Science, 1984)
Risk attitude and time preference are well-known and distinct concepts in the study of individuals' preferences for goods such as money. This paper reviews and explores the application of these concepts to the field of health. A mathematical model is presented, both in a general form and in an exponential form, which relates an individual's risk attitude in health to three effects—a quantity effect, a gambling effect and a time preference effect. It is shown that the overall risk attitude, as measured by its direction and magnitude, is merely the sum of the individual effects, as measured by their directions and magnitudes. Measurement methods are presented which can be used in a given situation to determine which effects are operating, in what directions and with what magnitudes. A new measurement procedure based on the temporary palliation of a chronic condition is described as a method of obtaining an individual's time preference pattern for health.